Emergency department thoracotomy of severely injured patients: an analysis of the TraumaRegister DGU® - Schulz-Drost, Stefan; Merschin, David; Gümbel, Denis; Matthes, Gerrit; Hennig, Friedrich; Ekkernkamp, Axel; Lefering, Rolf; Krinner, Sebastian (European Journal of Trauma and Emergency Surgery, 2019)
Aim of the study: Emergency department thoracotomy (EDT) may be the last chance for survival in some severe thoracic trauma. This study investigates a representative collective with the aim to compare the findings in Europe to the international experience. Moreover, the influence of different levels of trauma care is investigated. Methods: All emergency thoracotomies in patients with an ISS ≥ 9 from TR-DGU (2009–2014) within the first 60 min after arrival were identified. EDTs were identified separately, and mini thoracotomies and drainage systems were excluded. Results: 99,013 patients with sufficient data were observed. 1736 (1.8%) received thoracotomy during their hospital stay. 887 patients had a thoracotomy within the first hour in the emergency department (ED). 52.5% were treated in supraregional trauma centers (STC), 36.4% in regional (RTC) and 11.0% in local trauma centers (LTC). The mortality rates were 39.4% (STC), 20.9% (RTC) and 20.8% (LTC). The overall mortality rate showed no significant differences for blunt (28.2%) and penetrating trauma (31.3%). In case of cardiac arrest in the ED, a survival rate of 4.8% for blunt trauma and 20.7% for penetrating trauma was determined if EDT was carried out. Those patients showed a higher rate in severe thoracic organ injuries due to penetrating trauma but less extrathoracic injuries. Conclusion: Just over half of EDTs were performed in STC. Emergency room resuscitation followed by EDT had survival rates of 4.8% and 20.7% for blunt and penetrating trauma patients, respectively.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Chest trauma; Emergency room thoracotomy; Polytrauma; Resuscitative thoracotomy; Trauma registry